Phytochemical Profiling and Bioactivity Assessment of Colebrookea oppositifolia Sm. from the High Altitudes of Nepal's Far Western Region - Ojha, Anil; Pant, Prakash Raj; Dhami, Sabina Kumari; Dhami, Naresh Singh; Joshi, Prem Raj; Bhatta, Aarati; Singh, Nirajan Bahadur; Pant, Gunanand; Ojha, Tek Raj; Pant, Gajendra; Saud, Prem Singh (Far Western Review, 2025)
Traditional methods have made considerable use of herbal therapy to treat a variety of illnesses. This study aimed to quantify the levels of phenolic compounds and flavonoids in extracts made with two distinct solvents and evaluate their antibacterial qualities. Methanolic extract exhibited the highest concentration of bioactive compounds, with a total phenolic content (TPC) of 125.68 ± 2.67 mg gallic acid equivalents (GAE) per gram and a total amount of flavonoids (TFC) of 35.28 ± 3.22 mg quercetin equivalents (QE) per gram. Antibacterial assays revealed that both methanolic and extracts of hexane extracts efficiently inhibited Shigella sonnei, producing a zone of inhibition measuring 12 mm. These findings underscore the significant bioactive potential of the plant extracts under investigation, particularly those obtained using methanol and hexane solvents. Such properties render them promising candidates for the development of novel therapeutic agents aimed at treating infectious diseases.